Development of An Electronic-Based Parabolic Motion Material Module - Aprillia, Ajeng; Ngadimin, Ngadimin; Wahyuni, Agus (Universitas Lambung Mangkurat, 2022)
This study aims to produce an electronic-based parabolic motion material module that is suitable for use as teaching material. The research uses research and development methods (R&D) and 4-D models as development models. This study's subjects are x grade students at SMAN 8 Banda Aceh. The research instruments used are module assessments validated by experts and response questionnaires of teachers and students. Analyze data using a percentage formula. Data analysis of the module assessment sheet by experts involves two validators who conduct assessments in media and materials. The average percentage obtained in the media and material aspects is 74.6% and 89.5%, including decent and very decent. The average percentage obtained from the teacher and student response questionnaires was 83.6% and 85% and was included in the worthy or very good category. The study results can conclude that the electronic-based parabolic motion material module that has been developed is suitable for use as teaching material and is expected to develop the learning media in electronic-based modules further.